“It’s more like it doesn’t even exist” : stories of hauntings as a way of resisting colonial elimination of Sámi presence - Dankertsen, Astri (AlterNative: An International Journal of Indigenous Peoples, 2022)
In this article, I explore how haunting as a theoretical concept is useful for analyzing the emotional effects of colonization and forced assimilation of the Sámi, the Indigenous people in Norway, Sweden, Finland and Russia. While some still find it difficult to talk about what it means for them to be Sámi today, telling stories about hauntings is paradoxically something that they do more easily. Through theories concerning affect, emotions and haunting, I explore how these stories represent something more than elements of the Sámi religion. The act of telling these stories can also be analyzed as metaphors for both a continued connection that people have to the landscapes and their ancestors, and as a way of dealing with the emotional ambiguity of trying to find new ways of articulating a continuing Sámi presence. “It’s more like it doesn’t even exist”: stories of hauntings as a way of resisting colonial elimination of Sámi presence publishedVersion